2021
DOI: 10.1186/s12887-021-02803-z
|View full text |Cite
|
Sign up to set email alerts
|

Concentration levels of serum 25-Hydroxyvitamin-D and vitamin D deficiency among children and adolescents of India: a descriptive cross-sectional study

Abstract: Background Vitamin D is an essential micronutrient for the overall health and well-being of individuals. For strong musculoskeletal and neurological development of human body, vitamin D levels during childhood and adolescence have key importance. This is the first national-level study that analyzes the deficiency and concentration of serum 25-Hydroxyvitamin D [25(OH)D)] among Indian children and adolescents with respect to various demographic and socioeconomic characteristics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…A study conducted in England between 2008 and 2014 revealed a 15- fold rise in the number of young people with vitamin D insufficiency [ 10 ]. Similarly, a 2018 study in India showed that 41.9% of children and adolescents had inadequate levels of vitamin D [ 11 ]. Vitamin D deficiency can lead to poor bone formation and a higher risk of fractures [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in England between 2008 and 2014 revealed a 15- fold rise in the number of young people with vitamin D insufficiency [ 10 ]. Similarly, a 2018 study in India showed that 41.9% of children and adolescents had inadequate levels of vitamin D [ 11 ]. Vitamin D deficiency can lead to poor bone formation and a higher risk of fractures [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with higher socioeconomic status often lead more sedentary lives and may engage less in outdoor activities that expose them to sunlight. Conversely, adolescents from lower socioeconomic backgrounds tend to participate in outdoor activities and have prolonged exposure to sunlight, possibly due to their involvement in work alongside their parents [36][37][38][39]. Tese lifestyle distinctions can contribute to the varying prevalence of vitamin D defciency among wealth-related categories.…”
Section: Discussionmentioning
confidence: 99%
“…According to the CNNS, approximately 61% of Indian adolescents have insufficient vitamin D levels [ 29 ]. As cited in the previous studies, lifestyle factors and low dietary intake of vitamin D could be the possible reasons for high vitamin D deficiency in Indian adolescents [ 35 , 36 ]. India is deemed as the diabetes capital of the world [ 37 ].…”
Section: Discussionmentioning
confidence: 99%